Long-wavelength ion-sound parametric instability of plasma in magnetic field - Mikhailenko, V.S.; Ol'shansky, V.V.; Stepanov, K.N. (Вопросы атомной науки и техники, 2000)
We have studied numerically the dependence of the frequency and growth rate of the ion sound wave on the wave vector in plasma in the electric field of a helicon for long-wavelength oscillations when the wavelength of ion sound wave is equal to the order of magnitude to or exceeds the electron Larmor radius. Such instability may be separated if the pumping wave frequency (helicon) is equal to the order of magnitude to or less than the lower hybrid frequency. The growth rate approaches some tenth parts of the lower hybrid frequency if the electron drift velocity in the field of the helicon exceeds the ion sound velocity by some times. As for short wavelength oscillations, one should expect the anomalous damping of the helicon, turbulent heating of electrons and sustainment of gas discharge at the nonlinear stage of such instability.